The effectiveness of risk management practises in project performance in construction industry / Nur Amira Ayub and Nur Haazimah Ghazali - Ayub, Nur Amira; Ghazali, Nur Haazimah (2021)
The purpose of this research is to find out how well risk management practices in the construction industry affect project performance. This study was based on a random sample of 50 employees from a construction company. The point of the study is to evaluate the correlation between effective risk management and project performance. According to the findings of this study, understanding risk management, risk assessment, risk monitoring and risk identification have a vital role in project performance. Project managers need to guarantee that risk management approaches are not undertaken as a normal activity but as an essential project management tool to successfully and efficiently complete the task at hand. The remainder of the project team should be aware of the relevance of risk management approaches and how frequently they should be carried out, depending on the details of the task.